The host genetics affects gut microbiome diversity in Chinese depressed patients - Han, Ke; Ji, Lei; Wang, Chenliu; Shao, Yang; Chen, Changfeng; Liu, Liangjie; Feng, Mofan; Yang, Fengping; Wu, Xi; Li, Xingwang; Xie, Qinglian; He, Lin; et al. (Frontiers in Genetics, 2023)
The gut microbiome and host genetics are both associated with major depressive disorder (MDD); however, the molecular mechanisms among the associations are poorly understood, especially in the Asian, Chinese group. Our study applied linear discriminant analysis (LDA) effect size (LEfSe) and genome-wide association analysis in the cohort with both gut sequencing data and genomics data. We reported the different gut microbiota characteristics between MDD and control groups in the Chinese group and further constructed the association between host genetics and the gut microbiome. Actinobacteria and Pseudomonades were found more in the MDD group. We found significant differences in the ACE and Chao indexes of alpha diversity while no discrepancy in beta diversity. We found three associations between host genetics with microbiome features: beta diversity and rs6108 (p = 8.65 × 10–9), Actinobacteria and rs77379751 (p = 8.56 × 10–9), and PWY-5913 and rs1775633082 (p = 4.54 × 10–8). A species of the Romboutsia genus was co-associated with the species of Ruminococcus gnavus in an internetwork through four genes: METTL8, ITGB2, OTULIN, and PROSER3, with a strict threshold (p < 5 × 10–4). Furthermore, our findings suggested that the gut microbiome diversity might affect microRNA expression in the brain and influenced SERPINA5 and other spatially close genes afterward. These findings suggest new linkages between depression and gut microbiome in Asian, Chinese people, which might be mediated by genes and microRNA regulation in space distance.